5/8x2:3/4
2/3-2/4+3/8x2/5:4/6=?
1/8x2/6:3/4+5/3=???????
=1/24:3/4+5/3 =1/18+5/3 =31/18 Ủng hộ nka!!!!!
1/8*2/6:3/4+5/3
=1/8*1/3:3/4+5/3
=1/24*4/3+5/3
=1/18+30/18
=31/18
35\8x24\36
rút gọn ps
35/8*24/36 = 35/23*24/36 = 2/3
Bài 1: \(\dfrac{1}{3}\) + \(\dfrac{2}{4}\) + \(\dfrac{3}{5}\) ...........................3(>,<,=)
A.>
B.<
C.=
Bài 2: \(\dfrac{8x7-8x3}{8x2}\) = ?
A.2
B.3
C.4
D.5
Tìm x:
a).8x2 - 5=67
b).(4x - 2)4=16
`#3107`
a)
`8x^2 - 5 = 67 `
`=> 8x^2 = 67 + 5`
`=> 8x^2 = 72`
`=> x^2 = 9`
`=> x^2 = (+-3)^2`
`=> x = +-3`
Vậy, `x \in {-3;3}`
b)
`(4x - 2)^4=16`
`=> (4x - 2) = (+-2)^4`
`=> ` TH1: `4x - 2 = 2`
`=> 4x = 4`
`=> x =1`
TH2: `4x - 2 = -2`
`=> 4x = 0`
`=> x=0`
Vậy, `x \in {0; 1}.`
a) \(8x^2-5=67\)
\(8x^2=72\)
\(x^2=9\)
\(x=3\)
Vậy x = 3
b) \(\left(4x-2\right)^4=16\)
\(\left(4x-2\right)^2=4\)
\(4x-2=2\)
\(4x=4\)
\(x=1\)
Vậy x = 1
35\8x24\36
rút gọn các ps
làm nhanh mình t
x15 - 8x14 + 8x13 - 8x2 + ... - 8x2 + 8x – 5 với x
B = x15 - 8x14 + 8x13 - 8x2 + ... - 8x2 + 8x – 5 với x = 7
B = x15 - 8x14 + 8x13 - 8x2 + ... - 8x2 + 8x - 5
B = x^15 - 7x^14 -x^14+7x^13+x^13-7x^12-...-x^2+7x+x-5
B = x^14(x-7) - x^14(x-7) +...+x^2(x-7)-x(x-7)+x-5
B = 7-5=2
`B = x^15 - 7x^14 - x^14 + 7x^13 + x^13 - .... +7x + x - 7 + 2`
`<=> x^14(x-7) - x^13(x-7) + ... + x - 7 + 2`
`<=> (x^14-x^13 + ... + 1)(x-7) + 2`
Thay `x = 7 <=> (x^14 - x^13 + ... + 1) xx 0 + 2 = 2`.
B = \(x^{15}-8x^{14}+8x^{13}+8x^2+...-8x^2+8x-5\)
B = \(x^{15}-7x^{14}+x^{14}+7x^{13}+x^{13}+7x^{12}-...-x^2+7x+x-5\)
B = \(x^{14}\left(x-7\right)-x^{14}\left(x-7\right)+...+x^2\left(x-7\right)-x\left(x-7\right)-5\)
B = \(7-5=2\)
BT: Viết biểu thức sau về dạng bình phương hoặc dạng tích.
a, x4 - 8x2 + 16
b, (4x+5)2 - (5x+4)2
c, (2x-3)2 - 2(2x-3).(x+2) + (-x-2)2
a, \(x^4-8x^2+16=\left(x^2-4\right)^2\)
b, \(\left(4x+5\right)^2-\left(5x+4\right)^2=\left(4x+5-5x-4\right)\left(4x+5+5x+4\right)=\left(1-x\right)\left(9x+9\right)=9\left(1-x\right)\left(1+x\right)=9\left(1-x^2\right)\)
c, \(\left(2x-3\right)^2-2\left(2x-3\right)\left(x+2\right)+\left(-x-2\right)^2=\left(2x-3-x-2\right)^2=\left(x-5\right)^2\)
a) \(x^4-8x^2+16=\left(x^2-4\right)^2\)
b) \(\left(4x+5\right)^2-\left(5x+4\right)^2=\left(4x+5-5x-4\right)\left(4x+5+5x+4\right)=9\left(1-x\right)\left(x+1\right)\)c) \(\left(2x-3\right)^2-2.\left(2x-3\right)\left(x+2\right)+\left(-x-2\right)^2=\left(2x-3-x-2\right)^2=\left(x-5\right)^2\)